Understanding policy integration in the EU—Insights from a multi-level lens on climate adaptation and the EU's coastal and marine policy. Issue 82 (April 2018) - Russel, Duncan J.; den Uyl, Roos M.; de Vito, Laura
Highlights: Institutional environments are key to shaping how adaptation is integrated into key policy sectors. Investment in human resources for climate adaptation enhances institutional capacity for integrating climate change adaptation goals in vulnerable sectors. Financial mechanisms provide incentives to overcome barriers to the integration of climate change adaptation. Abstract: Integration of relatively new policy tasks like climate adaptation into established higher-level policy fields is insufficiently understood in the academic literature. This paper proposes a framework to evaluate the integration of climate adaptation into the sectoral policy-making of the European Commission, particularly following the publication of the EU Adaptation Strategy (in 2013). The paper uses a framework of micro, meso and macro-level institutional behaviour drawing strongly on new institutionalism perspectives to identify and explain factors enabling and hindering policy integration. It focuses on integration in the coastal and marine policy sector, which is expected to be particularly vulnerable to climate change impacts, and draws from data collected through a document review and interviews with key informants. The findings show that the integration of climate adaptation is still at an early stage. The integration process appears to be largely dependent on institutional dynamics at the EU-level combined with how member states and wider sectoral stakeholders engage with adaptation concerns. In particular, the ambivalence of some member states and a lack of urgency among sectoral stakeholders has hampered the integration of adaptation goals.